1987
DOI: 10.1093/nar/15.6.2417
|View full text |Cite
|
Sign up to set email alerts
|

Messemger RNA stability in Saccharomyces cerevisiae: the influence of transaltion and poly (A) tail length

Abstract: A comparison between the half-lives of 10 specific yeast mRNAs and their distribution within polysomes (fractionated on sucrose density gradients) was used to test the relationship between mRNA translation and degradation in the eukaryote Saccharomyces cerevisiae. Although the mRNAs vary in their distribution across the same polysome gradients, there is no obvious correlation between the stability of an mRNA and the number of ribosomes it carries in vivo. This suggests that ribosomal protection against nucleol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 39 publications
5
23
0
Order By: Relevance
“…An earlier study in yeasts (89) found no correlation between mRNA decay rates and poly(A) lengths, an observation supported by the work described here. We found that (i) poly(A)-deficient CYH2 and PGKI mRNAs are extremely stable (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An earlier study in yeasts (89) found no correlation between mRNA decay rates and poly(A) lengths, an observation supported by the work described here. We found that (i) poly(A)-deficient CYH2 and PGKI mRNAs are extremely stable (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The significance of such observations is still unclear. It is unlikely that arrested ribosomes simply protect mRNA from nucleases since, in normally growing cells, the ribosome packing density does not differ for stable and unstable mRNAs (89,94). The possibility exists that essential nucleases are metabolically unstable or that mRNA degradation depends on ribosomal translocation through or up to specific mRNA regions (9, 28).…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion is supported by our recent experiments which indicate that the entire set of D. discoideum ribosomal protein mRNAs can exist in the cytoplasm of early developing cells in a stable, but untranslated, form (83). A lack of a relationship between mRNA stability and translatability has also been observed in other experimental systems (38,71). To reconcile these conclusions with the destabilizing effects listed above, we note that all three types of effect lead to aberrant dissociation of mRNA from ribosomes.…”
Section: Discussionsupporting
confidence: 74%
“…Santiago et al (72) inhibited transcription with high concentrations of 1,10-phenanthroline, a chelating agent which affects a number of cellular processes (15,32,37) The possibility that poly(A) tail lengths directly determine mRNA stabilities has been suggested by microinjection experiments with adenylated and deadenylated mRNAs (17,29,46,56) and by experiments with cordycepin-treated cells (90). However, similar microinjection experiments with different poly(A)+ and poly(A)-mRNAs (16,27,48,73) and other experimental approaches (38,58,71,84) (Fig. 7) (58,59,75); (ii) the decay curves of mRNAs with half-lives longer than the 4-h half-life (58,59) for poly(A) shortening are linear, not biphasic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…shown that there is no apparent correlation between mRNA stability and transcript size (14), length of poly(A) tail (14,32), or efficiency of ribosome loading onto the mRNA (32). Even less is known about mRNA turnover during meiosis, primarily because of poor uptake of labeled precursors into cells during sporulation and reincorporation of radioactive isotopes from cells prelabeled during growth (due to RNA degradation during sporulation) (27,36).…”
mentioning
confidence: 99%